PANDEMI COVID-19 SEBAGAI ALASAN IMPEACHMENT PRESIDEN PRESPEKTIF HUKUM TATA NEGARA - Muchlisin Muchlis Muchlisin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
In the development of carrying trust as head of state as well as head of government, a president must execute the mandate that is contained in the law. This research was conducted to see the foundation used in the presidential impeachment, as well as whether the Covid-19 pandemic could be a reason for the president's impeachment. The author finds that there are several reasons for the impeachment in Indonesia, which is appropriate in security – Constitution 1945 Article 7A fourth amendment. States that the President and Vice-Presidents may be dismissed during his tenure by the MPR on the proposal of the DPR. In this case, of course, if it is proven to commit a violation of the law in the form of a blasphemy against the state, corruption, bribery, or other serious criminal acts.